Mutations in DNA Repair Genes and Clinical Outcomes of Patients With Metastatic Colorectal Cancer Receiving Oxaliplatin or Irinotecan-containing Regimens. (February 2021) - Marks, Eric I.; Matera, Robert; Olszewski, Adam J.; Yakirevich, Evgeny; El-Deiry, Wafik S.; Safran, Howard; Carneiro, Benedito A.
Abstract : Objectives: First-line regimens in the treatment of metastatic colorectal cancer (mCRC) combine a fluoropyrimidine with oxaliplatin (FOLFOX/XELOX) or irinotecan (FOLFIRI). There is limited efficacy data to guide the selection of one treatment over the other. This study investigated whether mutations affecting DNA damage response (DDR) could differentially influence the response to oxaliplatin and irinotecan-containing regimens. Methods: We retrospectively analyzed 49 patients with mCRC for whom treatment outcomes and results of comprehensive genomic profiling of tumors were available. Specimens with at least 1 pathogenic mutation involving BRCA1, BRCA2, ATM, BARD1, BRIP1, CDK12, CHEK1, CHEK2, FANCL, PALB2, PPP2R2A, RAD51B, RAD51C, RAD51D, or RAD54L were classified as DDR-mutated, while those without mutations were DDR-wild-type (WT). We compared the overall survival (OS), disease control rate, and response rate (RR) between the DDR-mutated and DDR-WT groups. Results: DDR mutations occurred in 11 patients (22%). First-line treatment with an oxaliplatin-containing regimen was administered to 33 patients (31 FOLFOX, 2 XELOX), while 16 patients received FOLFIRI. Among DDR-mutated cases, first-line treatment with FOLFOX/XELOX correlated with a statistically significant improvement in median OS compared with FOLFIRI (3.4 vs.1.8 y; P =0.042) and numerically higher RR (50% vs. 33%; P =0.58). No significant difference in OS (2.4 vs. 2.5 y; P =0.42), RR, disease control rate was observed between the 2 regimens in patients with DDR-WT tumors. Conclusions: Mutations in DDR genes were present in 22% of patients with mCRC. In patients with DDR-mutated tumors, initial treatment with FOLFOX/XELOX correlated with improved OS and a numerically higher RR compared with FOLFIRI.